Prevalence and Assessment of Experience of Dental Caries Among School Going Adolescents in A Rural Area of Sylhet, Bangladesh - Sony, Sadia Akther; Haseen, Fariha; Islam, Syed Shariful; Jahan, Ishrat (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Socio-epidemiological data of dental caries helps to plan effective community interventions. Objective: To estimate the prevalence and assess the experience of dental caries among school going adolescents in a rural area of Bangladesh. Methods: A cross-sectional study was donein Sylhet District in Bangladesh, between January and December of 2014. Students of class VIII, IX and X, aged 12-16 years were taken for the study. A total of 90 studentswere divided into 12-14 years and 15-16 years age groups using simple random sampling technique. A pre-designed, self-administered questionnaire was used for demographic survey. Students were examined for dental caries. Assessment of Experience of dental caries was done by Decayed, Missing and Filled teeth (DMFT) index. Results: The mean age of the respondents was 14.37±0.50 years. Females were 68(75.6%) and males were 22(24.4%). 31(34.4%), 30 (33.3%) and 29(32.2%) were from VIII, IX and X respectively. The older age group (15-16 years) had more decayed teeth than that of 12-14 years group (2.28 vs. 1.46; p=0.04). The mean DMFT score was lower in male compared to female (1.43 vs. 2.30; p>0.05).There was significant difference in the total DMFT score among the classes (p=0.009). Mean DMFT score was 1.88. Caries prevalence was 42.2% in the maxillary arch and 58.9% in the mandibular arch. Among males, the mandibular arch showed a higher caries level (63.64%) than the maxillary arch (40%), while in females, in maxillary and mandibular archeswere 42.64% and 42.65% respectively (p>0.05). Conclusion: 64.4% of the study population had dental caries with male predominance; mandibular arch was more involved. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 336-340